The effects of Omarigliptin on promoting osteoblastic differentiation. Issue 2 (20th December 2021) - Liao, Fake; Hu, Xiunian; Chen, Rijiang
ABSTRACT: Osteoporosis significantly impacts the normal life of the elderly and is reported to be closely related to dysfunction of osteoblastic differentiation. Runt-related transcription factor-2 (Runx2) is a critical transcriptional factor involved in the regulation of osteoblast differentiation. Omarigliptin is a novel dipeptidyl peptidase-4 (DDP-4) inhibitor and this study proposes to probe into its possible therapeutic function against Osteoporosis by investigating its impacts on osteoblastic differentiation. Osteogenic medium was used to induce osteoblastic differentiation in MC3T3‑E1 cells, and was verified by the increased alkaline phosphatase (ALP) activity, enhanced mineralization, and promoted expression level of osteoblastic differentiation-related factors, including bone morphogenetic protein-2 (BMP-2), ALP, osteocalcin (Ocn), collagen type I alpha 1 (Col1a1), Collagen Type I alpha 2 (Col1a2), Runx2, osterix (Sp7), fibroblast growth factor receptor 2 (Fgfr2), and fibroblast growth factor receptor 3 (Fgfr3), accompanied by the activation of the p38 and Akt pathways. After treatment with Omarigliptin, the ALP activity and mineralization were further promoted, accompanied by the further upregulation of osteoblastic differentiation-related factors, and activation of the p38 and Akt pathways. Lastly, Omarigliptin-induced osteoblastic differentiation, promoted ALP activity, and increased expression levels of Sp7, Fgfr2, Fgfr3, BMP-2, Ocn, ALP, Col1a1, and Col1a2, in the osteogenic medium- cultured MC3T3‑E1 cells were dramatically abolished by the knockdown of Runx2. Taken together, our data reveal that Omarigliptin promoted osteoblastic differentiation by regulating Runx2.